2021
DOI: 10.3390/diagnostics11101797
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Diagnostic Accuracy of Saliva-Based SARS-CoV-2 Screening in Educational Settings and Children Aged <12 Years

Abstract: Children have been disproportionately affected during the COVID-19 pandemic. We aimed to assess a saliva-based algorithm for SARS-CoV-2 testing to be used in schools and childcare institutions under pandemic conditions. A weekly SARS-CoV-2 sentinel study in primary schools, kindergartens, and childcare facilities was conducted over a 12-week-period. In a sub-study covering 7 weeks, 1895 paired oropharyngeal and saliva samples were processed for SARS-CoV-2 rRT-PCR testing in both asymptomatic children (n = 1243… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Accordingly, saliva has been shown to be a well-established diagnostic specimen for detecting SARS-CoV-2 RNA [ 18 , 19 , 20 , 21 , 22 ], a child-friendly sampling alternative to swab-based methods [ 23 , 24 ] and one potentially suitable for the mass screening of children [ 25 ]. The findings in our evaluation of the Salivette ® system confirmed that assessment [ 17 ].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Accordingly, saliva has been shown to be a well-established diagnostic specimen for detecting SARS-CoV-2 RNA [ 18 , 19 , 20 , 21 , 22 ], a child-friendly sampling alternative to swab-based methods [ 23 , 24 ] and one potentially suitable for the mass screening of children [ 25 ]. The findings in our evaluation of the Salivette ® system confirmed that assessment [ 17 ].…”
Section: Introductionsupporting
confidence: 84%
“…The study has some limitations: First, we cannot rule out false-negative results. Based on our experience from previous investigations (the sensitivity of the Salivette ® method in relation to oropharyngeal swabs was 94.9%), we consider this effect to be low [ 17 , 22 ]. Second, voluntary study participation may be associated with a selection bias, potentially over-representing participants with better adherence to infection control measures when in private or family settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few investigations that examined the suitability of chewed cotton pads, possibly due to an inconvenient workflow in the laboratory. One study demonstrated a significant agreement between nasopharyngeal swabs and saliva collected in a cotton pad device [16], and in other studies, rolled cotton achieved higher performance in the molecular diagnosis of an infection with SARS-CoV-2 [24][25][26][27]. Using a cotton pad to collect saliva was inferior to the collection of native saliva in a sterile container in our study.…”
Section: Discussionsupporting
confidence: 39%
“…In addition, this study could help saliva garner attention as a potential alternative specimen for diagnosing respiratory infections, despite the previously reported inconsistent diagnostic accuracy of saliva-based SARS-CoV-2 being dependent on the studied population or clinical settings. 3,4,14,15 Moreover, saliva collection is a noninvasive, easy, specimen acquirement method that requires no specific preparation, transportation, or storage.…”
Section: Discussionmentioning
confidence: 99%